Preparo e caracterização de materiais de eletrodos e eletrólitos para aplicação em supercapacitores flexíveis - Sandra Aparecida Alexandre (2019)
In the present work, eleven different supercapacitors (in the symmetric and asymmetric configurations) were prepared containing different active materials for the electrodes and ionogel type electrolytes. Themain focus of the research was the construction of flexible devices that provide high capacitances and energy densities (greater than 10 Wh Kg-1), without compromising the cyclability. The ionogels choicewas made in order to allows the construction of flexible supercapacitors (SCs). Three different ionogels were evaluated, which were prepared with the addition of ionic liquids (ILs) to poly (ionic liquids) matrices - PILs. Three matrices of PILs and three ILs were selected to have the same anion and similar cations in order to improve the compatibility between these compounds. The ionogels with 50wt% of IL were chosen once they provide good ionic conductivities and potential windows (2.5V), withoutcompromising the mechanical stability of the gels, thus allowing the construction of SCs in the sandwich configuration (electrode|ionogel|electrode) without the need of separators. For the preparation of ionogel 1 the PIL [EPIm] [FSI] and the IL [EMIm] [FSI] were used. For type 2 ionogel, the PIL [EPIm] [TFSI] and the IL [EMIm] [TFSI] were employed. In the type 3 ionogel, the PIL [A2M2Am] [TFSI] and the IL[MPPy] [TFSI] were chosen. The type I ionogel provided the highest values of ionic conductivity. The ionogels 1 and 2 exhibited gelationous appearance, providing good adhesion to the electrode materialsand thus, making possible the preparation of flexible supercapacitors. In contrast, ionogel 3, a waxy-like film, promoted detachment of electrode materials from current collectors, and it is therefore unsuitablefor the construction of flexible devices. The active materials of the electrodes were: (i) functionalized multi-walled carbon nanotubes (f-MWCNT), (ii) reduced graphene oxides (r-GO) and (ii) nanocomposites (r-GO: f-MWCNT). The composition of the nanocomposites was based on data from the literature that indicates that in this concentration the CNTs would act as spacers between the sheets of rGO, providing a larger surface area for the formation of the electrical double layer in theelectrode/electrolyte interface. The supercapacitors were prepared with these electrodes in the symmetrical configuration, ie both electrodes of the same material, and also in the asymmetric one with different electrodes (one electrode of r-GO and another electrode of f-MWCNT. The electrochemical characterization data showed that the asymmetric supercapacitor (r-GO|Ionogel 1|f-MWCNT) presented the best electrochemical performance providing high capacitance, energy and power densities, with little variation of these parameters over 2000 operating cycles. In this work, two important new contributionsto the state of the art of supercapacitors are highlighted: (i) the development of gel electrolytes of type PIL/IL (ionogels types 1 and 2) with high adhesion to the electrode materials (decreasing the contactresistances) and (ii) complete description of the behavior of the different solid and flexible supercapacitors with simultaneous determination of the voltage of the cells and the potentials of each electrode.